ANALISIS TERJEMAHAN GAYA BAHASA REPETISI DALAM NOVEL A THOUSAND SPLENDID SUNS, TEKNIK DAN KUALITASNYA (KAJIAN PENERJEMAHAN DENGAN PENDEKATAN STILISTIKA) - Murtafi, Anshoffy; Nababan, Nababan; Djatmika, Djatmika (PRASASTI: Journal of Linguistics, 2017)
ABSTRACT  Anshoffy Murtafi. S131208003. 2016. The Translation Analysis of Repetition Language Style In Novel A Thousand Splendid Suns. The Technicque And Quality (Translation Study Using Stylistics Approach). Supervisors: (1) Prof. Drs. M.R.Nababan, M.Ed, M.A., Ph.D. (2) Prof. Dr. Djatmika, M.A. Thesis. Postgraduated Program In Linguistics Majoring In Translation Studies. Sebelas Maret University. Surakarta.                A best-seller novel entitled "A Thousand Splendid Suns" by Khaled Hosseini translated by M. Nugrahani Berliani comes up with an interesting language use. It can be seen from the content that consists of a great number of language styles, and one of them is repetition that becomes the characteristic of this novel writer. This research aimed to (1) describe and identify the types of repetition language style in the novel A Thousand Splendid Suns, (2) describe the translation techniques used in the novel A Thousand Splendid Suns, and (3) describe the value and impact of the technique used in this study in term of accuracy and acceptability.               This research used descriptive qualitative method and focused to a single case. The data which were in the form of repetition language style in this study were obtained from the novel A Thousand Splendid Suns and its translations. Further, the data in the form of informant were gathered from the raters who assessed the accuracy and acceptability of the translation. The selected sampling technique was purposive sampling (theoretical based-sampling).  The data then were collected using document analysis and focus group discussion.               The conclusion of this study is the implementation of 10 translation techniques had a positive impact to the accuraracy and acceptability of its translation. The techniques giving positive impact in its translation in term of the accuracy and acceptability are established equivalence, generalization, transposition, amplification, pure borrowing, variation and particularization. Meanwhile, the techniques giving negative impact towards its translation in term of accuracy and acceptability are reduction, modulation, and discursive creation.  Keywords: Translation of Language Style, Repetition, A Thousand Splendid Suns, Stylistics